Import Deregulation: a Strategy to Improve Food Security in Indonesia - Jaya, Eni; Suprapti, Endang; Tarigan, Arihta Esther Br; Anggriani, Jum; Utama, Mohamad Wira (Sharia Journal and Education Center Publishing, 2025)
Food security remains a crucial challenge for Indonesia, a country with a large population facing climate uncertainty and limited domestic productivity. This study analyzes the role of import deregulation as a strategy to improve national food security. Through a comprehensive literature review and policy analysis, the article explores how non-tariff barriers, quota systems, and complex licensing processes have contributed to high domestic food prices compared to international market prices. The study shows that strict protectionist policies are often counterproductive to food accessibility, especially for low-income groups. The proposed deregulation strategy includes a transition from quota systems to more transparent tariffs, streamlining import licensing bureaucracy, and synchronizing national food data. The study argues that import deregulation, if managed with proper oversight, not only increases the physical availability of food but also strengthens food security through price stability and supply chain efficiency. These policy implications are expected to provide a framework for the government to balance the protection of domestic farmers with consumers' rights to affordable food.